The Oxford guide to effective writing and speaking how to communicate clearly - Seely, John. (Oxford Oxford University Press, 2013)
The Oxford Guide to Effective Writing and Speaking is the essential guide for everyone who needs to communicate in clear and effective English, both written and spoken. John Seely looks at the key factors to consider in tailoring your material so that you get your message across, such as understanding the demands of particular audiences, subjects, and situations.
Includes index.
Keywords: English language--Written English